Role of resveratrol in the management of insulin resistance and related conditions: Mechanism of action. (19th May 2017) - Abbasi Oshaghi, Ebrahim; Goodarzi, Mohammad Taghi; Higgins, Victoria; Adeli, Khosrow
Abstract: Resveratrol (RES), a well-known antioxidant, is present in numerous plant species and, as a result, is easily obtained through dietary intake of plant-based foods and beverages. Several studies suggest that RES has anti-carcinogenic, anti-microbial, and anti-viral effects. It may also have beneficial metabolic properties that result in mitigation of insulin resistance (IR) and related metabolic abnormalities, including dyslipidemia, hyperglycemia, and hyperinsulinemia through regulation of gene expression or the activity of rate-limiting enzymes. A large body of evidence supports the beneficial effects of RES in the management and treatment of IR, type 2 diabetes, and related complications through a multitude of mechanisms. This review article focuses on the mechanisms of action of RES, the mechanisms leading to improved insulin sensitivity, and its clinical role in the management and treatment of type 2 diabetes.